Potentiality of ghrelin as antioxidant and protective agent - Rachid Akki; Kawtar Raghay; Mohammed Errami (Taylor & Francis Group, 2021)
Background Oxidative stress is the result of cellular troubles related to aerobic metabolism. Furthermore, this stress is always associated with biological responses evoked by physical, chemical, environmental, and psychological factors. Several studies have developed many approaches of antioxidant defense to diminish the severity of many diseases. Ghrelin was originally identified from the rat stomach, and it is a potent growth hormone-releasing peptide that has pleiotropic functions. Methods A systematic review was conducted within PubMed, ScienceDirect, MEDLINE, and Scopus databases using keywords such as ghrelin, antioxidant, oxidative stress, and systemic oxidative stress sensor. Results In the last decade, many studies show that ghrelin exhibits protection effects against oxidative stress derived probably from its antioxidant effects. Pieces of evidence demonstrate that systemic oxidative stress increase ghrelin levels in the plasma. The expression of ghrelin and its receptor in ghrelin peripheral tissues and extensively in the central nervous system suggests that this endogenous peptide plays an important role as a systemic oxidative stress sensor Conclusion The current evidence confirms that ghrelin and its derived peptides (Desacyl-ghrelin, obestatin) act as a protective antioxidant agent. Therefore, stressor modality, duration, and intensity are the parameters of oxidative stress that must be taken into consideration to determine the role of ghrelin, Desacyl-ghrelin, and obestatin in the regulation of cell death pathways.